Analisis Kan’yoku Verba ”Dekiru” 「できる」 dalam Konteks Sosiolinguistik - Rosita Ningrum (Humaniora, 2011)
There are three kinds of Kan'youku or idiom verb "dekiru" "できる" namely, (1) 腹 が できる 'hara ga dekiru', meaning the stomach nutrients and when combined with the verb dekiru have had the sense of readiness / commitment, although not in any circumstances will be disappointed / angry, (2) 溝 が できる 'Mizo ga dekiru', Mizo means deep and narrow water channel and when combined with the verb dekiru mean gulf and (3) 耳 に 胼胝 が できる 'mimi ni Tako ga dekiru , mimi means ear and Tako means bones. When combined with the verb dekiru means formed bones in the ear. Idiom is closely associated with the flexibility to speak more than one functional or grammatical level of a language. Someone must have a full understanding of the context of the idiom is to use it properly; because idiom words can be translated literally. By studying the idioms, learners can enter into a language and its roots, in this case cultural roots in the language being studied and how to present it as a form of communication, not merely in its grammatical form.